CREATIVITY OF CONTEMPORARY DIEVTURI GROUPS AS A CULTURAL POLITICAL DISCOURSE - Ozoliņš, Gatis (Via Latgalica, 2009)
Dievturība (dievturi - "God keepers", "people who live in harmony with God") is a newly created religious tradition having appeared in the second part of the 1920s – 1930s, its most essential source includes materials of Latvian folklore and folk traditions. These are interpreted by construing a religious ethical theory and creating a religion which is alternative to Christianity, with its own doctrine and rituals, and the conception of Latvianness in culture and politics. Latvianness is the most essential concept of cultural politics to which all activities of the dievturi are subjected (exaltation, family celebrations (krustabas, vedības (marriage), bedības (funeral)) as well as seasonal rituals, cultural historical excursions, tidying and spiritual restoration of the sacral sites (sacred places, castle mounds), folklore activities, article publications in mass media, summer thematic camps in the countryside marked by intensive mastering and cultivation of history and culture, celebration of Latvian public holidays and the most important remembrance days. Contemporary dievturi groups are seeking for new ideas in order to develop and popularize their conceptions, which can partly be characterized as a cultural political programme for theoretical (doctrine) and practical (exaltations, ceremonies, seasonal rituals) realization of Latvianness and its components. Within this publication, creativity means the system of ideas and values that promotes the development and perspectives of dievturi groups as well as includes them into a wider cultural political environment thus performing a culture-creating job. A special attention is paid to the essential ideas and values guiding the creativity of contemporary Latvian dievturi groups, making ample use of storyteller habitus, thus intentionally allowing the domination of group participant discourse. The two main directions of dievturi group participant creativity are the development of their doctrine (teaching) and the ritual practice (exaltations). These directions allow to attract wide attention of the society and mass media, new participants and supporters, to influence the political and cultural processes in Latvia. An important part in the doctrinal reflections of the dievturi, especially in the ritual practice (exaltations), has always been taken by Latvian literature writings. A selective choice of these supplement the textual canon of the dievturi continuing the tradition in line with “the mood of Latvian folk songs” and attributing a more modern shape and world outlook concepts to dievturi undertakings. The aim of an exaltation is always associated with the main cultural political concept of the dievturi – Latvianness, namely, to make Latvianness more active, to offer an opportunity to approach Latvianness, make efforts for deeper comprehension of it, being aware and living through it, although thematically it may be dedicated to separate components of Latvianness (people, land, language, God, Māra, Laima, work, virtues, human life, and the like). Also, the most essential ideas and values of dievturība – gender equality, domesticity, antiglobalism, ecology, traditional marriage formula, life style and appearance, environment (for example, use of Latvian language), music, art and literature priorities (classical and/or national music, use of local building materials and ornaments (all ornaments have been observed in Latvia’s nature), writers, poets and playwrights who most precisely depict the “Latvian spirit” – derive from folk songs and the cultural concepts deriving thereof. Activity in the field of Latvianness (ethnicity conception) is in accord with the activity in favour of the future of the Latvian people, symbolical non-forgetting of culture correspond to generating of culture. This attributes a political and social dimension to the cultural activity of dievturi. Dievturība does not perform an official cultural politics of cultural values, heritage, traditions etc., this is a task for politicians; however, it is at least a marginal participant of the cultural political sphere. Placing ethnicity, or the Latvian discourse, at the centre of cultural politics encompasses the range of further impact when the seeming encapsulation within the margins of culture are replaced by reflections on Latvian economy, guidelines in education and science, health care system, axiological juxtaposition of the countryside and city. Also, the evaluation and criticism of the activity of the Christian Church by the dievturi is connected with the conception of Latvianness. Dievturi strongly disclaim Christianity and any chance of mutual cooperation (and also vice versa), protest against its monopoly position in Latvian society, consider Christianity a historically alien religion having been forced upon Latvians and demanding the status of a traditional religion in Latvia also for dievturība including, for example, the right to wed, to celebrate religious festivals. The results of field research do not allow to speak about dievturība today as a strong and united manifestation of Latvian religious experience and way of life. Rather, it is possible to register (after the decline of the movement at the end of the 1990s and at the beginning of the 2000s) a quite consistent and sufficiently active revival which is connected with the appearance of new persons and creative ideas among Latvian dievturi. The future events depend on the fact whether dievturi themselves would be able to solve the protracted inner inconsistencies and find a uniting grounds for further development of the movement. The article is based on the study results obtained during the 2006–2008 field research carried out in dievturi groups (interviews with group leaders, participants and individual representatives, transcripts of audio and video materials). The study was carried out with the financial support of the project “Society and lifestyles” and using its accepted methods – ethnographic description, semi-structured interviews and methods of visual anthropology (photography, filming) and instructions by the Ethical Commission (for example use of assumed names for storytellers).